Rapid Landscape Changes in Plastic Bays Along the Norwegian Coastline - Bastesen, Eivind; Haave, Marte; Andersen, Gidske L.; Velle, Gaute; Bødtker, Gunhild; Krafft, Charlotte Gannefors (Frontiers in Marine Science, 2021)
The Norwegian Coastal Current transports natural debris and plastic waste all along the Norwegian coastline. Sinks typically include so-called “wreck bays”, which are largely unchanged over centuries, controlled by tidal movements, prevailing winds, coast morphology and ocean currents. We recently mapped over 350 “wreck bays” along a 70 km coastline of the southwest Norway, and in this study we will focus on case studies where we believe dramatic landscape changes is a likely result of long term accumulation of marine plastic litter. The bays are predominantly southwesterly (facing the dominating wind direction) and typically consists of narrow inlets and rocky beaches. The natural foreshore deposition consists of storm deposited seaweed, kelp, timber and volcanic pumice, which during the last decades have become mixed with plastic. We have compared historical aerial photos (pre-plastic) with recent aerial images and collected systematic soil profiles of the substratum around these wreck bays. Our hypothesis is that marine plastic accumulation accelerates the formation of the near shore soil layer, when organics are entangled with and kept in place by layers of plastic. The deposits are preventing natural drainage of near shore wetlands and ponds, and in some cases, river outlets are blocked. These hypothesis is supported by transects showing a base layer of 5-10 cm layer of compact, plastic free soil or sediment, often associated with an accumulation of pumice, under a 40-70 cm layer of organic rich, wet soil mixed with plastic. In some cases the plastic sediment is deposited directly on bare rocks faces. Aerial photos indicate that some ponds have indeed increased in size from 1960 to 2015, unlike the natural succession where ponds are filled with vegetation and become marshes over time. Our study describes and illustrates the landscape and vegetation changes, which is synchronous with occurrence of mismanaged plastic waste along the coasts of North Sea. Relative dating of the soil layers and volumetric calculations indicate up to 50 years of accumulation with thick layers of soil intermixed with plastic in the affected bays.